PREVALENCE OF DISEASES COMPLICATION IN INDIVIDUALS WITH TYPE TWO DIABETES MELLITUS - Oktaviana, Riast Eka; Sari, Rosella Dwi Komala (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Non-communicable diseases are a special problem, especially in Indonesia, one of the developments of non-communicable diseases is diabetes mellitus. This disease can be characterized by glucose levels in the blood which will have a negative impact on damage to body organs such as blood vessels, heart, eyes, nerves, and kidneys. Type 2 diabetes (T2DM) is the most common case of diabetes, this occurs when the body's resistance occurs or does not produce enough insulin. Diabetes mellitus has contributed to the development of diabetes complications both microvascular and macrovascular. Microvascular complications can include neuropathy, retinopathy, and nephropathy, while macrovascular complications are more likely to lead to coronary artery disease, cerebrovascular disease, and peripheral vascular disease. Based on the above findings, this study was conducted to determine the prevalence of microvascular and macrovascular complications that may occur at Jasmine Clinic 2 Surakarta. Management and Outcome : A case report conducted in this study by reconding the numbers and informations from data based of T2DM patients in Jasmin 2 Clinic, Surakarta. All necessary data such as gender, age, duration of diabetes, recent blood sugar levels (both fasting blood sugar and hemoglobin A1c calculations were entered) as well as recent complaints obtained through phone interviews. Based on the data presented, there were a total of 100 participants, of which 52 were women and 48 were men, aged 40 – 80 years. All participants received oral information regarding the purpose of this research. This study found prevalence of DM in women was higher than men by 52% and 48% respectively. There were 33% people aged less than 60 years. As many as 52% of individuals with diabetes mellitus 1-5 years, 32% for 6-10 years, and more than 10 years by 16%. Current blood sugar levels 14% blood sugar levels <100mg/dl and the remaining 86% with blood sugar levels >100mg/dl. The incidence of microvascular complications reported higher than macrovascular complications, there were 68% and 8% for each, while participants who did not have complaints were 24%. Conclusion : This study declared higher prevalence of DM among women aged over or 60 years. Hyperglycemia is a tendency as dominant factor developing microvascular and macrovascular complications in individuals with T2DM.